BRANDING RIAU THE HOMELAND OF MELAYU DALAM MEMPEROMOSIKAN PARIWISATA PROVINSI RIAU - Munir, Berlianti; Arief, Andi M Rifiyan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Riau branding The Homeland Of Malay is selogan or branding that can be analyzed i.e. Land Spilled Blood. The branding on the critical limits stretcher the Riau Provincial Government to promote tourism potential flagship (the best) that had become the main tourist attraction of Riau with the hope of being able to increase levels of tours visit foreign countries or overseas in moving the wheel of economic society, improve the image of the area of regional competitiveness, and national and international dikancah. This research aims to know the meaning of Branding Riau The Homeland Of Malay In Riau Province to promote tourism. Branding is the name, Logo, and other Visual Identity. This study uses qualitative methods with the descriptive approach to discuss the issue. As for the subject Researches in this study as many as three people, taken using Key Informant. While the data collection technique in the research of using observation, documentation and interviews. With a variable into sub main component Branding (Temporal) is divided into easy to Spelt, easy to pronounce, unusual and unique, Memorable, protected, and recognized in General. From the results of research conducted in the field with research on Branding Riau The Homeland Of Malay In Riau Province to promote tourism including average.Keywords: Branding In Asia, Riau, The Homeland Of Malay